Analyzing hydriding performance in full-scale depleted uranium beds. (15th February 2020) - Yun, Seongjin; Gwak, Geonhui; Ghasemi, Masoomeh; Choi, Jaeyoo; Ju, Hyunchul
Abstract: In this study, the hydrogen absorption characteristics of depleted uranium (DU) are analyzed using a three-dimensional transient DU hydride model. The DU model is first validated using experimental data taken from a copper foam-based DU hydride bed, where it is found that the simulation results agree well with the experimental DU temperature evolution and hydriding time. Using the experimentally validated model, we then compare two DU bed designs: one designed to contain 1.86 kg of DU for a tritium capacity of 70 g and loaded with the copper foam to enhance the internal heat transfer during the exothermic hydrogen absorption process, and the other based on copper fins and 5.26 kg of DU to increase a hydrogen isotope (tritium and deuterium) capacity. The simulation results for full-scale DU beds reveal differences in the DU hydriding behavior of the two DU designs, information that is useful in the development of optimal bed design strategies to achieve optimal hydrogen charging performance. Highlights: We have studied the characteristics of DU hydride such as local H/U ratio. The DU temperature and equilibrium pressure affect hydrogen absorption performance. The effective thermal conductivity is key factor to performance of DU hydride. Increasing DU temperature creates a tradeoff between absorption kinetics and Peq .